Associations between muscle‐building exercise and alcohol use behaviors among adolescent boys: Results from the 2019 Youth Risk Behavior Survey. Issue 3 (28th March 2022) - Ganson, Kyle T.; Testa, Alexander; Rodgers, Rachel F.; Jackson, Dylan B.; Nagata, Jason M.
Abstract: Background and Objectives: To explore the association between muscle‐building exercise (MBE) and alcohol use behaviors among adolescent boys. Methods: Data from the 2019 Youth Risk Behavior Survey ( N  = 4120) were analyzed using multiple logistic regressions. Results: A greater number of days of MBE in the past week was associated with higher odds of four alcohol use behaviors, including recent alcohol use and binge drinking. Discussion and Conclusions: Findings extend prior research showing relationships between team sports participation and alcohol use behaviors. Scientific Significance: This study is the first to examine associations between MBE and alcohol use behaviors among adolescent boys.